THE CENTRAL BANKS’ POLICY RESPONSE TO COVID-19 PANDEMIC - Topić-Pavković, Branka (Politeia, 2020)
During the past few months, the world has been battling an unexpected and invisible threat. It has challenged all aspects of life in dealing with economic, humanitarian, and social consequences. At the moment, the economic impacts of the corona crisis are still a puzzle, but the fact is that the largest crisis in the recent history caused by a pandemic will lead to a global recession. In times of crisis, a policy-mix strategy is necessary and implies the inclusion of respective Central Banks in providing adequate measures of monetary policy for economic and financial recovery. The aim of this paper is to identify and аnalyse measures taken by respective Central Banks in order to mitigate the damage caused by the virus crisis and help national economies in recovery. Reactivation of non-standard measures applied in the previous financial crisis shows that the standard instruments and targets of such institutions are insufficient in emergency circumstance. The comparative analysis conducted will show how Central Banks of the largest economies and the region responded to the corona virus challenge, with particular reference to the Central Bank of Bosnia and Herzegovina. The results show that Central Banks opted for unconventional monetary policy measures reflected in quantitative easing, zero interest rates, and swap lines in order to alleviate the negative effects of the emerging crisis. Exceptional measures will be needed to ensure recovery in response to the coronavirus and the rapid deterioration of the global economy. The specificity of the monetary arrangement in Bosnia and Herzegovina has once again proved to be a constraint in the implementation of economic policy measures in extraordinary circumstances.